2023
DOI: 10.1158/2159-8290.cd-22-1131
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted MDM2 Degradation Reveals a New Vulnerability for p53-Inactivated Triple-Negative Breast Cancer

Abstract: Triple negative breast cancers (TNBC) frequently inactivate p53, increasing their aggressiveness and therapy resistance. We identified an unexpected protein vulnerability in p53-inactivated TNBC and designed a new PROTAC to target it. Our PROTAC selectively targets MDM2 for proteasome-mediated degradation with high-affinity binding and VHL recruitment. MDM2 loss in p53 mutant/deleted TNBC cells in 2D/3D culture and TNBC patient explants, including relapsed tumors, causes apoptosis, while sparing normal cells. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 90 publications
2
21
0
Order By: Relevance
“…This newly developed compound, AC-03-087 (JG-03-111) (Figure 3I), showed potent PARP1 binding affinity in the HTRF competitive displacement assay against the fluorescent probe, JG-03-142, with low nanomolar affinity of AC-03-087 for PARP1 (IC50 = 3.07 ± 0.881 nM) compared to Olaparib (IC50 = 1.42 ± 0.335 nM) (Figure S3C). We also evaluated AC-03-087 for its ability to form a ternary complex using the AlphaScreen technology 26,27 and confirmed that AC-03-087 treatment induces a stable ternary complex between PARP1 and MDM2 (Figure S3D). In line with these data, dose escalation experiments conducted with AC-03-087 in HeLa cells using an In-Cell Western assay 28 confirmed specific degradation of PARP1 at low nanomolar concentrations (Figure 3J).…”
Section: ■ Resultsmentioning
confidence: 60%
“…This newly developed compound, AC-03-087 (JG-03-111) (Figure 3I), showed potent PARP1 binding affinity in the HTRF competitive displacement assay against the fluorescent probe, JG-03-142, with low nanomolar affinity of AC-03-087 for PARP1 (IC50 = 3.07 ± 0.881 nM) compared to Olaparib (IC50 = 1.42 ± 0.335 nM) (Figure S3C). We also evaluated AC-03-087 for its ability to form a ternary complex using the AlphaScreen technology 26,27 and confirmed that AC-03-087 treatment induces a stable ternary complex between PARP1 and MDM2 (Figure S3D). In line with these data, dose escalation experiments conducted with AC-03-087 in HeLa cells using an In-Cell Western assay 28 confirmed specific degradation of PARP1 at low nanomolar concentrations (Figure 3J).…”
Section: ■ Resultsmentioning
confidence: 60%
“…Remarkably, our results are consistent with recent findings that MDM2 p90 depletion leads to cancer cell death regardless of p53 mutation status. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that our findings are consistent with recent studies showing that, in triple‐negative breast cancer, MDM2 p90 elimination by MDM2‐PROTAC resulted in cell death regardless of the p53 mutation status, accompanied by the posttranscriptional stabilization of p73 but not p63. [ 28 ] The upregulation of p73 was confirmed to be a consequence of MDM2 p90 depletion and was crucial for cell death induction, although the exact mechanism remains unknown. It was speculated that MDM2 p90 depletion completely eliminates its p53‐dependent and p53‐independent oncogenic effects, including p73 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many compounds that can reactivate p53 or destabilize mutant p53, such as APR‐246 and COTI‐2, have been approved for clinical trials 32 . At the same time, MDM2 inhibitors have also been related to research, and inhibition of MDM2–p53 interaction has become a possible therapy 33–37 . However, the corresponding research has mainly focused on the mutation site of TP53 or p53, and the relevant clinical transformation is still in its infancy 38 .…”
Section: Introductionmentioning
confidence: 99%